2021
DOI: 10.3389/fonc.2021.642130
|View full text |Cite
|
Sign up to set email alerts
|

Does Subtelomeric Position of COMMD5 Influence Cancer Progression?

Abstract: The COMMD proteins are a family of ten pleiotropic factors which are widely conserved throughout evolution and are involved in the regulation of many cellular and physiological processes. COMMD proteins are mainly expressed in adult tissue and their downregulation has been correlated with tumor progression and poor prognosis in cancer. Among this family, COMMD5 emerged as a versatile modulator of tumor progression. Its expression can range from being downregulated to highly up regulated in a variety of cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…Interestingly, Zou et al demonstrated that CASP8 inhibited PD-L1 expression by upregulating A20 expression and that decreased CASP8 was associated with sensitivity to anti-PD-L1/PD-1 immunotherapy [ 47 ]. Amplification of TRIO and COMMD5 proteins has also been reported in various types of cancer, suggesting an oncogenic function [ 48 , 49 ]. Hence, our TIME-related signature incorporating these six DEASs might be helpful for early diagnosis and prevention in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Zou et al demonstrated that CASP8 inhibited PD-L1 expression by upregulating A20 expression and that decreased CASP8 was associated with sensitivity to anti-PD-L1/PD-1 immunotherapy [ 47 ]. Amplification of TRIO and COMMD5 proteins has also been reported in various types of cancer, suggesting an oncogenic function [ 48 , 49 ]. Hence, our TIME-related signature incorporating these six DEASs might be helpful for early diagnosis and prevention in clinical practice.…”
Section: Discussionmentioning
confidence: 99%